Antioxidant Activity, Total Phenolic Content, and Total Flavonoid Content of Methanol Extract of Vernonia elaeagnifolia Leaves Using ABTS and DPPH Assays - Sari, Asti Arum; Wulandari, Febri; Adiningsih, Minda Ustavia (Universitas Muhammadiyah Surakarta, 2025)
Vernonia elaeagnifolia, also known as Vernonia elliptica, is a member of the Asteraceae family and is known to contain phenol and flavonoid compounds. The study examining the activity of these active compounds in this plant is limited. Therefore, this study aimed to evaluate the phytochemical profile, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity of the methanol extract of V. elaeagnifolia leaves. Phytochemical screening was conducted using tube tests, while TPC and TFC were measured using the Folin-Ciocalteu and aluminium chloride colorimetric methods, respectively. Antioxidant activity was assessed using ABTS and DPPH assays. Phytochemical screening revealed the presence of alkaloids, saponins, flavonoids, and polyphenols in the methanolic extract. Quantitative analysis showed that TPC and TFC values were 81.26 ± 0.62 mg GAE/g and 54.02 ± 0.70 mg QE/g, respectively. The extract showed moderate antioxidant activity, with IC50 values of 139.81 ± 0.62 µg/mL (ABTS) and 166.62 ± 3.72 µg/mL (DPPH), which were significantly different. These findings suggest that the ABTS assay is more effective in evaluating the antioxidant activity of V. elaeagnifolia leaf extract compared to the DPPH assay, and V. elaeagnifolia leaves have potential as a source of natural antioxidants. Further isolation and characterization of active compounds are recommended